2021
DOI: 10.3390/polym13091359
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bending Test Method for Polymer Railway Sleeper Materials

Abstract: Alternative sleeper technologies have been developed to address the significant need for the replacement of deteriorating timber railway sleepers. The review of the literature indicates that the railway sleepers might fail while in service, despite passing the evaluation tests of the current composite sleeper standards which indicated that these tests do not represent in situ sleeper on ballast. In this research, a new five-point bending test is developed to evaluate the flexural behaviour of timber replacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
0
0
3
Order By: Relevance
“…Örnek olarak AREMA normu (Chapter 30-35) bu alternatif traverslerin elastisite modülünün en az 1,17 GPa olmasını isterken, Japon standartları (JIS E 1203:2007) 6 GPa minimum değerini vermekte, yeni Avustralya standardı (AS1085.22:2020) ise herhangi bir elastisite modülü belirtmemektedir. ISO 12856 standardı ise 1,17 GPa ile 6 Gpa şartlarına haiz 3 kategorili bir yöntem sunmaktadır [41].…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Örnek olarak AREMA normu (Chapter 30-35) bu alternatif traverslerin elastisite modülünün en az 1,17 GPa olmasını isterken, Japon standartları (JIS E 1203:2007) 6 GPa minimum değerini vermekte, yeni Avustralya standardı (AS1085.22:2020) ise herhangi bir elastisite modülü belirtmemektedir. ISO 12856 standardı ise 1,17 GPa ile 6 Gpa şartlarına haiz 3 kategorili bir yöntem sunmaktadır [41].…”
Section: Introductionunclassified
“…Traverslerin elastisite modülleri ve kütleleri ise, hat rijitliğini ve tüm demiryolu sisteminin davranışını etkilemektedir ve gerek hat rijitliği açısından gerekse Şekil 1'de izah edilen yüksek etki hızlı dinamik yüklere dayanımı açısından büyük öneme sahiptir [39]. Birçok farklı travers üzerinde yapılan test ve analizler sonucunda, traverslerin eğilme modüllerinin, balast modülünden dahi önemli olduğu ve ray mesnedindeki eğilme momentinin (sagging), travers merkezindeki eğilme momentine (hogging) oranının, travers modülü gereğinden fazla yüksek veya düşük olması halinde arttığı belirlenmiştir [41]. Dolayısıyla yüksek servis ömrü ve performans için traverslerin optimum elastisite modülüne ve yeterli yüksek kütleye sahip olması gerekmektedir.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The interaction between the central components meaning rails, sleepers, and the ballast bed in dynamic load cases is particularly interesting. Literature has shown that the sleeper's mechanical properties strongly influence the total stiffness of the track and its long-term settlement behaviour and has more impact than the support modulus of the ballast bed [1,2,3]. In laboratory tests it was shown that under static loading soft sleepers develop a pronounced W-shaped deflection profile along their length and apply less uniformly distributed pressure onto the ballast bed with pressure peaks directly below the rails [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Literature has shown that the sleeper's mechanical properties strongly influence the total stiffness of the track and its long-term settlement behaviour and has more impact than the support modulus of the ballast bed [1,2,3]. In laboratory tests it was shown that under static loading soft sleepers develop a pronounced W-shaped deflection profile along their length and apply less uniformly distributed pressure onto the ballast bed with pressure peaks directly below the rails [2,3,4]. However, in long-term experiments with numerous load cycles a hogging shape of the sleeper was observed because the resilient movement of the sleeper ends lead to substantial gapping in that region, which can accelerate ballast deterioration due to impact loads and thus sleeper settlement [4,5].…”
Section: Introductionmentioning
confidence: 99%